Effective school district leadership : transforming politics into education - Leithwood, Kenneth A. (SUNY series in educational leadership., 1995)
Annotation The authors describe how effective superintendents work with their immediate staffs, elected trustees, and school-based administrators. Each chapter examines the meaning of effective district leadership from different perspectives.